PENINGKATAN LITERASI NUMERASI MELALUI MODUL PBL KAIDAH PENCACAHAN BERBANTUAN VIDEO SCRIBE - Saputra, Reksa; Elvina, Nova (Jurnal Visi Ilmu Pendidikan, 2026)
This research is a type of research and development (R&D) utilizing the ADDIE model, which comprises five stages: analysis, design, development, implementation, and evaluation. The scope of this research is limited to the development of an E-module. Thus, this article aims to develop a Problem-Based Learning (PBL) assisted E-module for teaching counting principles using Video scribe to enhance appropriate numeracy literacy skills and receive positive feedback from students, making it suitable for use in teaching. Student responses were gathered from Grade X students at SMAN 1 Jawilan. The average score from the material experts' questionnaire was 3.75, which falls into the valid category; the media experts' average score was 3.85, also categorized as valid; and the education experts' average score was 3.7, categorized as valid. The average score from the student response questionnaire was 86%, which is categorized as very practical for use in teaching. Therefore, the results indicate that the developed E-module is feasible and effective for use.